WAWASAN AL-QUR’AN TENTANG OTORITAS AGAMA DALAM BERDAKWAH - Faliha Syaifi Jannah; Muhammad Alif (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study aims to thematically analyze the Qur'anic insights on religious authority in da'wah (Islamic propagation), focusing on three main aspects: (1) types of authority forms in da'wah, (2) reasons for the use of such authority, and (3) the impacts of using authority in contemporary contexts. This research employs a qualitative approach using the Structured Thematic Analysis (STA) method, which adopts the principles of Grounded Theory. The primary data sources are Qur'anic verses related to da'wah authority, supported by credible exegeses such as Tafsir al-Misbah, Tafsir Ibn Kathir, and Tafsir al-Maraghi. The findings indicate that the Qur'an teaches seven forms of da'wah authority, all of which culminate in wisdom, gentleness, truthful and impactful speech, patience, and repelling evil with goodness. The use of authority is driven by theological reasons such as collective obligation (farḍ kifāyah) and the status of the best community (khayr ummah), yet it is bounded by the principle that the duty of the preacher (dā'ī) is only to convey the message, not to coerce. The impact of a correct understanding of da'wah authority is the emergence of a moderate attitude that respects religious freedom and individual responsibility. This study is expected to contribute to the development of Islamic da'wah as a mercy to all worlds (raḥmatan lil 'ālamīn) in the contemporary era.